EDUKASI BANK SAMPAH UNTUK MENINGKATKAN KESADARAN PENGELOLAAN SAMPAH BERKELANJUTAN DI KELURAHAN WATES KOTA MAGELANG - Sukarniati, Lestari; Amalia Lubis, Firsty Ramadhona; Az Zakiyyah, Nurul Azizah; Jaya Putra, Budi; Deni Marwanto, Arnufan (Jurnal Pengabdian Masyarakat Berkarya, 2025)
Urban waste management issues require innovative solutions that involve active community participation. The Waste Bank program emerges as a community-based waste management initiative that adopts a banking system to provide economic value to sorted waste. This community service activity aims to increase the understanding and awareness of residents in RW 2, Wates Village, Magelang City regarding the concept, mechanism, and benefits of the Waste Bank. The implementa tion methods include socialization, education, and evaluation using pre-test and post-test instruments to measure the improvement in public knowledge. The results show that the Waste Bank program provides three main benefits: economic benefits through additional income, improved discipline in waste management, and the creation of a clean and healthy residential environment. The success of the program is reflected in the increased public awareness of the importance of waste sorting at its source and the active participation of residents in sustainable waste management. This program contributes to the principles of 4R (Reduce, Reuse, Recycle, and Recovery/Replace) to establish an environmentally friendly and sustainable waste management cycle.